2016
DOI: 10.1093/ehjqcco/qcw025
|View full text |Cite
|
Sign up to set email alerts
|

Impact of co-morbid burden on mortality in patients with coronary heart disease, heart failure, and cerebrovascular accident: a systematic review and meta-analysis

Abstract: Abstract:Aims: We sought to investigate the prognostic impact of co-morbid burden as defined by the Charlson comorbidity index (CCI) in patients with a range of prevalent cardiovascular diseases. Methods & Results:We searched MEDLINE and EMBASE to identify studies that evaluated the impact of CCI on mortality in patients with cardiovascular disease. A random effects meta-analysis was undertaken to evaluate the impact of CCI on mortality in patients with coronary heart disease (CHD), heart failure (HF) and cere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
63
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 73 publications
(68 citation statements)
references
References 61 publications
3
63
0
2
Order By: Relevance
“…However, care must be taken in interpreting this result because it is possible that other unmeasured comorbidities were present in the older adults that may have biased the estimates. 36,37 Our findings have important implications regarding care and outcomes in women, particularly as patients with AMI are living much longer. 38 We clearly showed that the gap in mortality between the sexes decreased for STEMI and almost disappeared for NSTEMI after adjusting for treatments at discharge.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…However, care must be taken in interpreting this result because it is possible that other unmeasured comorbidities were present in the older adults that may have biased the estimates. 36,37 Our findings have important implications regarding care and outcomes in women, particularly as patients with AMI are living much longer. 38 We clearly showed that the gap in mortality between the sexes decreased for STEMI and almost disappeared for NSTEMI after adjusting for treatments at discharge.…”
Section: Discussionmentioning
confidence: 87%
“…Age was significantly associated with excess mortality even after adjusting for sex, comorbidities, and treatments. However, care must be taken in interpreting this result because it is possible that other unmeasured comorbidities were present in the older adults that may have biased the estimates 36, 37…”
Section: Discussionmentioning
confidence: 99%
“…These reflect variables which are not captured but which are related to both (nonblinded) treatment allocation and to outcome. Among these are factors such as frailty and noncardiovascular comorbidity . However, in this particular work, clinical assessment of frailty or multimorbidity would be expected to lead to use of Ticagrelor or Prasugrel in “less frail”/multimorbid patients overall; and hence any confounding in this regard should favor outcomes in the potent P2Y12 groups.…”
Section: Discussionmentioning
confidence: 99%
“…Comorbidities rarely occur in isolation, with patients having multiple comorbid conditions that may impact on a patient's clinical course synergistically, rather than in isolation. Data on the influence of global measures of comorbid burden and their impact on clinical outcomes are relatively limited, and mainly derived from small cohorts limited to single centres . In the Nobori‐2 study, the risk of cardiac mortality post PCI in patients with a high global comorbid burden as defined by the Charlson comorbidity score was quadruple compared to cohorts with no comorbid conditions …”
Section: Introductionmentioning
confidence: 99%
“…Data on the influence of global measures of comorbid burden and their impact on clinical outcomes are relatively limited, and mainly derived from small cohorts limited to single centres. 2,4 In the Nobori-2 study, the risk of cardiac mortality post PCI in patients with a high global comorbid burden as defined by the Charlson comorbidity score was quadruple compared to cohorts with no comorbid conditions. 2 The Elixhauser classification system 10 (ECS) is one of the most commonly used measures of comorbid burden and comprises 30 comorbidity measures used to derive a weighted comorbidity score (van Walraven Elixhauser comorbidity score) to assess global comorbid burden.…”
Section: Introductionmentioning
confidence: 99%